KEDUDUKAN HUKUM HARTA PERKAWINAN DALAM PERKAWINAN SIRRI DALAM PERSPEKTIF HUKUM INDONESIA - Isetyowati Andayani; Raden Besse Kartoningrat (Trunojoyo Madura University, 2022)
Marriage is a human right that is protected by laws and regulations, the role of the state in regulating the occurrence of marriage. The marriage that occurs causes a series of legal relationships that occur both before and after the marriage. One of the objects of the legal relationship is the existence of marital property. In this study using normative research as well as a law approach and a conceptual approach. This study will examine more deeply about the position of assets from the results of sirri marriages in the legal perspective in Indonesia. If their marriage is legal then the consequences of their marital property can also be enjoyed by husband and wife so that the opposite applies if the marriage is not valid then their marital property will not benefit them. . Sirri (secret) marriages, or often sirri marriages, are known to those who are Muslim. Sirri marriages are unregistered marriages. In the Compilation of Islamic Law (KHI) the rules for those who are Muslim. Also do not know sirri marriage. KHI also regulates the obligation to register marriages, in addition to fulfilling the pillars and requirements of marriage.